Improving the Leakage Characteristics and Efficiency of GaN-based Micro-Light-Emitting Diode with Optimized Passivation. (15th May 2020) - Lee, Da-Hoon; Lee, Jung-Hoon; Park, Jin-Seong; Seong, Tae-Yeon; Amano, Hiroshi
Abstract : We investigated the effect of atomic layer deposition (ALD) Al2 O3 (50 nm)/plasma-enhanced chemical vapour deposition (PECVD) SiO2 (250 nm) and PECVD SiO2 (300 nm) passivation layers on the leakage current and efficiency of InGaN-based micro-LEDs with different sizes. Regardless of passivation layers, the leakage current increased with decreasing LED size and increasing reverse bias. Emission microscopy examination showed that with increasing reverse bias, the number of defect-related emission spots and their intensities increased. For the micro-LEDs <50 μ m, the emission spots were mainly located at the sidewall regions. Above −10 V, the single PECVD SiO2 passivation layer gave higher leakage current than the double ALD-Al2 O3 /PECVD-SiO2 layer. The micro-LEDs with the single passivation layer gave the ideality factors of about 2.0, while that with the double layer exhibited values smaller than 2.0. The micro-LEDs with the double passivation layer exhibited external quantum efficiency peaks at lower current density compared to those with the single layer. It was shown that smaller micro-LEDs were more sensitively dependent on the types of the passivation layers. These results exhibit that the ALD-Al2 O3 /PECVD-SiO2 passivation layer is more effective in suppressing the sidewall damage-induced current than the PECVD-SiO2 layer.